Severity of Periodontal Status in Type I and Type II Diabetes Mellitus - Rida Batool, Munir Ahmed Banglani, Shazia Parveen Rajper, Nida Talpur, Salman Shams, Seema Imtiaz, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the severity of periodontal status in patients with type1 and type 2 diabetes mellitus. The study was conducted in diabetic clinic Liaquat University hospital, Hyderabad. Study design: It was a descriptive cross sectional study. Setting: This study was conducted at diabetic clinic Liaquat University hospital, Hyderabad. Data Collection Procedure: After meeting the inclusion criteria, 178 patients of diabetes mellitus type 1 and type 2, from diabetic clinic Liaquat University Hospital, (Hyderabad) were assessed to record their oral findings, to check for the presence of periodontal disease and record severity associated, with the help of CPITN index (Community Periodontal Index of Treatment Need). A (WHO-probe), also known as special dental CPI-probe, used for the relevant examination. Patients after relevant examination were advised treatment that they required. For that purpose they were referred. Results: The sample of 178 patients which were divided in two groups equally. Among 89 patients of type 1 DM, 60 patients scored 1 according to CPITN scoring (bleeding on probing, which showed presence of periodontal disease). In comparison, among 89 patients of type 2 DM, 51 patients scored 3 according to CPITN scoring (which means pathological pocket depth (4-5) which showed more severity of periodontal disease.). The relationship of CPITN scoring was significant with both types of DM (p value=0.001). Conclusion: This study concluded that patients of type 2 DM showed more severity of periodontal status than patients of type 1 DM.